Dopamine acting at D1-like, D2-like and alpha 1-adrenergic receptors differentially modulates theta and gamma oscillatory activity in primary motor cortex - ŞEHİRLİ, ÜMİT SÜLEYMAN (PUBLIC LIBRARY SCIENCE, 2017)
The loss of dopamine (DA) in Parkinson's is accompanied by the emergence of exaggerated theta and beta frequency neuronal oscillatory activity in the primary motor cortex (M1) and basal ganglia. DA replacement therapy or deep brain stimulation reduces the power of these oscillations and this is coincident with an improvement in motor performance implying a causal relationship. Here we provide in vitro evidence for the differential modulation of theta and gamma activity in M1 by DA acting at receptors exhibiting conventional and nonconventional DA pharmacology. Recording local field potentials in deep layer V of rat M1, co- application of carbachol (CCh, 5 mu M) and kainic acid (KA, 150 nM) elicited simultaneous oscillations at a frequency of 6.49 +/- 0.18 Hz (theta, n = 84) and 34.97 +/- 0.39 Hz (gamma, n = 84). Bath application of DA resulted in a decrease in gamma power with no change in theta power. However, application of either the D1-like receptor agonist SKF38393 or the D2-like agonist quinpirole increased the power of both theta and gamma suggesting that the DA-mediated inhibition of oscillatory power is by action at other sites other than classical DA receptors. Application of amphetamine, which promotes endogenous amine neurotransmitter release, or the adrenergic alpha 1-selective agonist phenylephrine mimicked the action of DA and reduced gamma power, a result unaffected by prior co- application of D1 and D2 receptor antagonists SCH23390 and sulpiride. Finally, application of the alpha 1-adrenergic receptor antagonist prazosin blocked the action of DA on gamma power suggestive of interaction between alpha 1 and DA receptors. These results show that DA mediates complex actions acting at dopamine D1-like and D2-like receptors, a1 adrenergic receptors and possibly DA/alpha 1 heteromultimeric receptors to differentially modulate theta and gamma activity in M1.
Keywords: RAT PREFRONTAL CORTEX; HIPPOCAMPUS IN-VITRO; TRANSCRANIAL MAGNETIC STIMULATION; MEMBRANE-POTENTIAL OSCILLATIONS; LOCUS-CERULEUS ACTIVATION; FAST-SPIKING INTERNEURONS; DEEP-BRAIN-STIMULATION; PARKINSONS-DISEASE; SUBTHALAMIC NUCLEUS; ADRENERGIC-RECEPTORS